The importance of social capital for young People's active transport and independent mobility in rural Otago, New Zealand. (November 2019) - Porskamp, Tessa; Ergler, Christina; Pilot, Eva; Sushama, Preeti; Mandic, Sandra
Abstract: Social capital influences adolescents' licenses for active transport and independent mobility, through parental decision making and safety concerns, and may contribute to increasing adolescents' physical activity. Drawing on 20 parental interviews and 11 focus groups (73 adolescents) from rural New Zealand, this paper shows the importance of social capital and social trust for active transport and independent mobility in an under researched rural context. Change over time in social capital, social trust and parental safety concerns limited adolescents' active transport and independent mobility. Health policy should incorporate social capital measures to increase adolescents' active transport, independent mobility and physical activity. Highlights: Social capital influenced rural youths' transport and independent mobility behaviors. Barriers to independent mobility were viewed as too great for actual behaviour change. Concerns for personal and traffic safety had negative influence. Rural parents perceived decrease in social capital since their childhood. Social capital should be included in health policies targeting physical inactivity.